Comparison of Magnetic Field Maps by Direct Measurement and Reconstruction Using Boundary Element Methods - Alexander Hinton; Alexander Bainbridge; Olli Tarvainen (Metrology, 2025)
Boundary Element Methods (BEMs) can be applied to determine the value of the magnetic field at any point within a domain if the magnetic field components are measured on the surface of the domain. For large magnetic volumes, BEMs provide an attractive alternative to fine three-dimensional Hall probe scans for determining the local shape of the field as the fields can be evaluated inside the volume with an arbitrary position and with a reduced measurement time. BEMs have been applied to the field data measured on the boundary of three-dimensional Hall probe scans for two example magnets, which have been measured at STFC Daresbury Laboratory, UK. The fields reconstructed using BEMs are compared to the fields directly measured during the Hall probe scans. The reconstructed fields can be calculated to within 1 mT rms of the directly measured fields. For the transverse field components greater than 1 mT, the fields can be reconstructed to within 5% rms of the directly measured fields.